Case Report: A Novel Homozygous Missense Variant of FBN3 Supporting It Is a New Candidate Gene Causative of a Bardet–Biedl Syndrome–Like Phenotype - Genovesi, Maria Luce; Torres, Barbara; Goldoni, Marina; Salvo, Eliana; Cesario, Claudia; Majolo, Massimo; Mazza, Tommaso; Piscopo, Carmelo; Bernardini, Laura (Frontiers in Genetics, 2022)
Fibrillin proteins are extracellular matrix glycoproteins assembling into microfibrils. FBN1, FBN2 and FBN3 encode the human fibrillins and mutations in FBN1 and FBN2 cause connective tissue disorders called fibrillinopathies, affecting cardiovascular, dermal, skeletal and ocular tissues. Recently, mutations of the less characterized fibrillin family member, FBN3, have been associated in a single family with Bardet-Biedl syndrome (BBS). Here we report on a patient born from two first cousins and affected by developmental delay, cognitive impairment, obesity, dental and genital anomalies, brachydactyly/syndactyly. His phenotype was very similar to that reported in the previous FBN3-mutated family and fulfilled BBS clinical diagnostic criteria, although lacking polydactyly, the most recurrent clinical feature , as the previous siblings described. A familial SNP-array and proband’s WES were performed prioritizing candidate variants on the sole patient’s Runs of Homozygosity. This analysis disclosed a novel homozygous missense variant in FBN3 (NM_032447:c.5434A>G; NP_115823:p.Ile1812Val; rs115948457), inherited from the heterozygous parents. This study further supports that FBN3 is a candidate gene for a BBS-like syndrome characterized by developmental delay, cognitive impairment, obesity, dental, genital and skeletal anomalies. Anyway, additional studies are necessary to investigate the exact role of the gene and possible interactions between FBN3 and BBS proteins.